Arterial Baroreflex Dysfunction Fails to Mimic Parkinson's Disease in Rats - Jian-Guang Yu; Jian Wu; Fu-Ming Shen; Guo-Jun Cai; Jian-Guo Liu; Ding-Feng Su (Elsevier, 2008)
Patients with Parkinson's disease (PD) often have attenuated baroreflex function, which may occur before the onset of PD-associated movement disorders. The aim of the present study was to test whether impaired arterial baroreflex (ABR) function could contribute to the pathogenesis of PD. 6-Hydroxydopamine (8 μg in 4 μl) was microinjected into the left substantia nigra of rats to establish unilateral PD models, and bilateral PD models were established in rats by administration of rotenone by osmotic minipump for four weeks, at a dose of 2.5 mg ⋅ kg−1 ⋅ day−1. An ABR dysfunction model was obtained by performing sinoaortic denervation (SAD). Hemodynamic variables were determined in conscious rats. PD-like symptoms and dopamine content in corpus striatum (CS) were also assessed. 6-Hydroxydopamine and rotenone treatment and SAD were associated with enhanced blood pressure variability (BPV) and blunted baroreflex sensitivity (BRS). Rotenone, but not SAD, significantly reduced dopamine content in the CS, induced catalepsy, and inhibited rearing and exploratory behavior. SAD before the administration of rotenone did not aggravate the rotenone-induced dopaminergic lesion. Our findings do not support the presumption that ABR dysfunction contributes to the pathogenesis of PD in rats. Keywords:: arterial baroreflex, Parkinson's disease, baroreflex sensitivity, blood pressure variability, sinoaortic denervation